Effects of habitat complexity on urban bee occupancy eclipse those of urbanization and flower diversity - Jason Pho; Cheyenne Davis; Colby Kapp; Evelyn Guerrero; Nina S. Fogel; Adam B. Smith; Nicole E. Miller-Struttmann (Biological Conservation, 2026)

Acoustic Monitoring of Two Seagrass Meadows Reveals Differences in Oxygen Ebullition and Biomass - Megan S. Ballard; Kyle A. Capistrant-Fossa; Kevin M. Lee; Andrew R. McNeese; Colby W. Cushing; Robert T. Taylor; Thomas S. Jerome; Kenneth H. Dunton; Preston S. Wilson (Estuaries and Coasts, 2026)

Cancer Risk and Mortality Following Kaposi Sarcoma Among People with HIV in the United States, 2000 to 2019 - Sally Peprah; Eric A. Engels; Qianlai Luo; Analise Monterosso; Colby H. Cohen; Ruth M. Pfeiffer; Meredith S. Shiels (Cancer Causes & Control, 2026)
People with HIV (PWH) have increased Kaposi sarcoma (KS) risk. Among 2,645 PWH with KS in the United States HIV/AIDS Cancer Match Study, subsequent cancer risk was elevated 2.8-fold (95% confidence interval [CI]: 2.4–3.3) compared to PWH without KS. Mortality after KS declined 2000–2002 and 2012–2015 (hazard ratio = 0.64; 95%CI: 0.55–0.74).

Movements of Galapagos Sharks (Carcharhinus galapagensis) in Eastern Tropical Pacific Waters off Central and South America - Bradley M. Wetherbee; Guy M.C. Harvey; Colby D. Kresge; Mary K. Brantley; Owen W. Fleischer; Nicole A. Kobasa; Jeremy J. Vaudo; Mahmood S. Shivji (Fishes, 2025)
Galapagos sharks (Carcharhinus galapagensis) are a large species belonging to the family Carcharhinidae, with poorly understood biology, especially along continental coastlines, which limits effective management of their populations. Here, we report preliminary findings of their movements along the Pacific Coast of Panama and Colombia, derived from satellite telemetry. Sharks were tracked for as long as 1.5 years, during which they moved extensively (~400 km along the Panama/Colombia coastline), with areas with high concentrations of detections that spanned the Panama/Colombia border. Sharks appeared to alter their movements during the diel cycle (more detections at night) and in relation to the wet/dry seasons (more detections during the dry season). Locations of shark detections were most commonly within 20 km of shore and in water less than 100 m deep, although detections were recorded hundreds of kilometers from shore in water thousands of meters deep. Galapagos sharks appear to move more extensively along continental coastlines compared to island locations, where most previous information about their movements and biology has been obtained.

Coproducing a Technology Readiness Level framework for non-persistent genetic biocontrol of aquatic invasive species - Julie Badger; Rex Alirigia; Isabel Ameli; Przemek Bajer; Bill Bartodziej; Vinita Dalgleish; Siba Das; Justine Dauphinais; Meg Duhr; Jeff Forester; Stephen Frankenberg; Rebeca Gutierrez-Moreno; et al. (Journal of Environmental Management, 2025)

Modeling aerosol bolus inhalations in the human lung with the multiple path particle deposition model: Comparison with experimental data - B. Asgharian; O. Price; A.A.T. Borojeni; A.P. Kuprat; S. Colby; R.K. Singh; R.A. Corley; C. Darquenne (Journal of Aerosol Science, 2025)

Dust transport pathways from The Great Basin - Ronald S. Treminio; Nicholas P. Webb; Saroj Dhital; Akasha Faist; Beth Newingham; Colby Brungard; David DuBois; Brandon L. Edwards; Emily Kachergis (Aeolian Research, 2025)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Paralog switching facilitates diadromy: ontogenetic, microevolutionary and macroevolutionary evidence - Rebecca S. Colby; Stephen D. McCormick; Jonathan P. Velotta; Elizabeth Jockusch; Eric T. Schultz (Oecologia, 2024)

Bronchioalveolar organoids: A preclinical tool to screen toxicity associated with antibody-drug conjugates - Tara N. McCray; Vy Nguyen; Jake S. Heins; Elizabeth Nguyen; Kristen Stewart; Colby T. Ford; Calvin Neace; Priyanka Gupta; David J. Ortiz (Toxicology and Applied Pharmacology, 2024)

Automated bidirectional coupling of multiscale models of aerosol dosimetry: Validation with subject-specific deposition data - A.P. Kuprat; O. Price; B. Asgharian; R.K. Singh; S. Colby; K. Yugulis; R.A. Corley; C. Darquenne (Journal of Aerosol Science, 2023)

Barriers and Facilitators to a Healthy Community Environment During COVID-19: Perceptions of Extension Nutrition Educators and Other Key Community Stakeholders - E. Varela; J. Zeldman; A. Kuch; Y. Wang; M. Shushari; E. Hall; J. McNamara; J. Morrell; T. Tolar-Peterson; O. Brown; M. Olfert; L. Franzen-Castle; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Consensus Paper: Cerebellum and Ageing - Angelo Arleo; Martin Bareš; Jessica A. Bernard; Hannah R. Bogoian; Muriel M. K. Bruchhage; Patrick Bryant; Erik S. Carlson; Chetwyn C. H. Chan; Liang-Kung Chen; Chih-Ping Chung; Vonetta M. Dotson; Pavel Filip; et al. (The Cerebellum, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Application of a Two-Analyte Integrated Population Pharmacokinetic Model to Evaluate the Impact of Intrinsic and Extrinsic Factors on the Pharmacokinetics of Polatuzumab Vedotin in Patients with Non-Hodgkin Lymphoma - Dan Lu; Tong Lu; Rong Shi; Leonid Gibiansky; Priya Agarwal; Colby S. Shemesh; Randall C. Dere; Uzor Ogbu; Jamie Hirata; Pascal Chanu; Sandhya Girish; Jin Yan Jin; et al. (Pharmaceutical Research, 2020)
Purpose The established two-analyte integrated population pharmacokinetic model was applied to assess the impact of intrinsic/extrinsic factors on the pharmacokinetics (PK) of polatuzumab vedotin (pola) in patients with non-Hodgkin lymphoma (NHL) following bodyweight-based dosing. Methods Model simulations based on individual empirical Bayes estimates were used to evaluate the impact of intrinsic/extrinsic factors as patient subgroups on Cycle 6 exposures. Intrinsic factors included bodyweight, age, sex, hepatic and renal functions. Extrinsic factors included rituximab/obinutuzumab or bendamustine combination with pola and manufacturing process. The predicted impact on exposures along with the established exposure-response relationships were used to assess clinical relevance. Results No clinically meaningful differences in Cycle 6 pola exposures were found for the following subgroups: bodyweight 100–146 kg versus 38–<100 kg, age ≥ 65 years versus <65 years, female versus male, mild hepatic impairment versus normal, mild-to-moderate renal impairment versus normal. Co-administration of rituximab/obinutuzumab or bendamustine, and change in the pola manufacturing process, also had no meaningful impact on PK. Conclusions In patients with NHL, bodyweight-based dosing is adequate, and no further dose adjustment is recommended for the heavier subgroup (100–146 kg). In addition, no dose adjustments are recommended for other subgroups based on intrinsic/extrinsic factors evaluated.

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Abstinence-induced withdrawal severity among adolescent smokers with and without ADHD: disentangling effects of nicotine and smoking reinstatement - L. Cinnamon Bidwell; Sara G. Balestrieri; Suzanne M. Colby; Valerie S. Knopik; Jennifer W. Tidey (Psychopharmacology, 2018)

Late Holocene fluctuations of Quelccaya Ice Cap, Peru, registered by nearby lake sediments - Justin S. Stroup; Meredith A. Kelly; Thomas V. Lowell; Colby A. Smith; Samuel A. Beal; Joshua D. Landis; Pedro M. Tapia (Journal of Quaternary Science, 2015)
Records of clastic sediment from lakes that receive glacial meltwater provide a means for inferring past glacial fluctuations. However, increased clastic sedimentation has been interpreted to indicate both glacial advance and recession. Here we examine the timing of clastic sediment deposition in Challpacocha, a glacially fed lake located downvalley from Quelccaya Ice Cap (QIC), Peru, in comparison with known ice cap margin fluctuations. Using a comparison with a nearby non‐glacial lake, Yanacocha, we document that a record of clastic sediment flux from Challpacocha reflects meltwater‐derived sediment. We then compare the clastic sediment record from Challpacocha with the Qori Kalis glacier moraine record. We find that organic‐rich sediment was deposited primarily during the late Holocene advance of QIC (before ∼CE 1490). In contrast, clastic sediment was deposited during QIC recession (∼CE 1490–1970). Peaks in clastic sediment flux are associated with the onset of ice retreat. We suggest that this pattern of clastic sediment deposition reflects changing meltwater production and/or glacial erosion during ice advance and retreat and supports models of increased clastic sedimentation during ice retreat.

Thermosensitive Liposome Formulated Indocyanine Green for Near-Infrared Triggered Photodynamic Therapy: In Vivo Evaluation for Triple-Negative Breast Cancer - Colby S. Shemesh; Delaram Moshkelani; Hailing Zhang (Pharmaceutical Research, 2015)

Growth responses of Sphagnum hollows to a growing season lengthening manipulation in Alaskan Arctic tundra - H. Genet; S. F. Oberbauer; S. J. Colby; C. L. Staudhammer; G. Starr (Polar Biology, 2013)

Near-Infrared Image-Guided Delivery and Controlled Release Using Optimized Thermosensitive Liposomes - David C. Turner; Delaram Moshkelani; Colby S. Shemesh; David Luc; Hailing Zhang (Pharmaceutical Research, 2012)

REPRODUCTIVE SEASONALITY OF WESTERN ATLANTIC BOTTLENOSE DOLPHINS OFF NORTH CAROLINA, U.S.A. - Victoria G. Thayer; Andrew J. Read; Ari S. Friedlaender; David R. Colby; Aleta A. Hohn; William A. McLellan; D. Ann Pabst; Jennifer L. Dearolf; Nan I. Bowles; John R. Russell; Keith A. Rittmaster (Marine Mammal Science, 2003)
A bstract We describe reproductive seasonality of bottlenose dolphins in North Carolina (NC), U.S.A., using strandings data from the entire coast of NC and sighting data from Beaufort, NC and by estimating dates of birth of known females. We found a strong peak of neonate strandings in the spring (April‐May), and low levels of neonate strandings in the fall and winter. The distribution of neonate strandings was significantly different from a uniform distribution ( P K = 3.8). We found a unimodal distribution of 282 sightings of neonates with a diffuse peak in the summer. The temporal distribution of sightings of neonates departed significantly from a uniform distribution (P K = 5.1). Estimated birth dates of neonates from known females occurred in May ( n = 6) and June ( n = 4), with a single fall birth. These methods shed light on bottlenose reproductive patterns and underscore the value of using information from multiple types of data. Clarification of bottlenose dolphin reproductive patterns, such as the seasonality of birth, may enhance our understanding of the population structure of this species in the mid‐Atlantic region.

Turning On and Off with Excitation: The Role of Spike-Timing Asynchrony and Synchrony in Sustained Neural Activity - Boris S. Gutkin; Carlo R. Laing; Carol. L. Colby; Carson C. Chow; G. Bard Ermentrout (Journal of Computational Neuroscience, 2001)

Effects of naltrexone with nicotine replacement on smoking cue reactivity: preliminary results - K. E. Hutchison; Peter M. Monti; Damaris J. Rohsenow; Robert M. Swift; Suzanne M. Colby; Maryann Gnys; Raymond S. Niaura; Alan D. Sirota (Psychopharmacology, 1999)